The Intellectual and Developmental Character of Cardinal Newman’s University Preaching Style - Edward Ondrako (Cahiers Victoriens et Edouardiens)
A preacher’s sermons ought to have ‘a peculiarity, an identity of style, which enables one to recognize the author at a glance,’ in John Henry Newman’s view. The intellectual and developmental character of his sermons have a consistency and distinctive theory and epistemology of faith. With this in mind, the essay examines several key events and examples of his university preaching style beginning with his final sermon to the university faculty at Oxford in 1843, through his time in Dublin in 1856, with a final look at his acceptance speech when named a Cardinal in 1879. There is a brief comparison of his preaching style to two of his Discourses on Mary in 1849 which are polemical and hortatory. Newman’s aim in university preaching was to cultivate a theology of the heart and gave a persuasive example by his humble contemplation of God.